2015
DOI: 10.17140/goj-1-103
|View full text |Cite
|
Sign up to set email alerts
|

The Histamine H4 Receptor: A Novel Target for Safe Anti-inflammatory Drugs?

Abstract: The functional role of histamine H 4 receptors (H 4 Rs) in the Gastrointestinal (GI) tract is reviewed, with particular reference to their involvement in the regulation of gastric mucosal defense and inflammation. H 4 Rs have been detected in different cell types of the gut, including immune cells, paracrine cells, endocrine cells and neurons, from different animal species and humans; moreover, H 4 R expression was reported to be altered in some pathological conditions, such as colitis and cancer. Functional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…E.g. it is possible to (1) suppress H4R in gastrointestinal cells with JNJ-7777120, to use (2) maraviroc to hamper infection via gp120 and use (3) Interestingly, Adami [M. Adami and G. Coruzzi (2014)] found that the H4R antagonist JNJ-7777120 is able to undo the gastric damage of indomethacin. The "ok" in the tox column of table-1 is based on their finding.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…E.g. it is possible to (1) suppress H4R in gastrointestinal cells with JNJ-7777120, to use (2) maraviroc to hamper infection via gp120 and use (3) Interestingly, Adami [M. Adami and G. Coruzzi (2014)] found that the H4R antagonist JNJ-7777120 is able to undo the gastric damage of indomethacin. The "ok" in the tox column of table-1 is based on their finding.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Much of the drug research in H 4 R field is focused on the search for H 4 R antagonists because of possibilities for the treatment of different inflammatory conditions, e.g. skin diseases, airway diseases or bowel diseases . However, preclinical results show also utility of H 4 R ligands in cancer, neuropathic pain or vestibular disorder .…”
Section: Structures and Histamine H4r Affinities Of Synthesized Compomentioning
confidence: 99%
“…11,16 HRH4 is of particular importance for regulating immune cell functions, including chemotaxis and cytokine secretion, whereas HRH4 antagonists have shown anti-inflammatory, antihyperalgesic, and anti-allergic effects in several acute and chronic experimental rodent models. [17][18][19][20] We have previously reported that genetic depletion of Hrh4 and the anti-HRH4 chemicals in mice suppressed laser-induced CNV (laser-CNV). 21 Macrophages play a major role in ocular angiogenesis, including CNV in wet-AMD.…”
Section: Introductionmentioning
confidence: 99%